(3ebGdI aj GdMQha heG jJQcH efgGs - (3YHO Gddg Hf GdWjH GdHZOGOj , nCoHh GdnanQL GHf GdpqWpqjH , J (B435 (3g` s
(3ChdgG (B:s
(3GdYdI GdJi ef CLdgG dGjUhJ HGdMQa faSI heaQOkG dCfg ZGjI hGdZGjI dGJfbSe hGdUhJ jfbSe s
(3BNQgG (B:s
(3hGdYdI ai JSejI GdMQa MQakG HbjGS JhdOg agh CHOkG dGjYO HGdCWQGa dGHGdeJhSWGJ , hdG JfbVi GdebGdI hGdhGgH GdYbd GdMeO hGdefI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B13s
(3fSNI fajSI LOkGs
(3eUOQ GbJfGA GdCUd (B:s
(3ESchQjGd (B(888/3) s
Keywords: (3GdadSaI hGdefWbs